Analisis Kesalahan Penggunaan Modalverben dalam Kalimat Bahasa Jerman - Handayani, Fiterah; Al-ilmullah, Syarifah Fathimah; Syamsurijal, Syamsurijal (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This study aims to obtain data on the types of errors in the use of Modalverben and to find out the factors that cause errors erros in class XII students of Sma Negeri 2 Pangkep. This research is descriptive qualitative. The error analysis method proposed by Ellis in Tarigan. The population in this study ware XII grade students consisting of 4 classes namely MIA 1, MIA 2, IIS 3 and IIS 4 with a total of 124 students. The research sample was purposive sampling and the  sampel taken was class XII IIS 3 consisting of 32 students. Data were collected through written test and questionnaire. The results of the data analysis show that the average error in the use of Modalverben in German is very high category with a total of 623 errors. The selection of Modalverben that does not fi the context(42,54%), improper conjugation of Modalverben(30,65%) and placement of Modalverben in the sentence structure (26,81%). The factors causing errors are dividedinto two categories of internal factors, namelylack of understanding of the material, lack of attention while learning, learning concentration, learning motivation an the influence of Indonesian lenguage while external factors include teaching methods, limited learning facilities and intensity of practiceKeywords: Error Analysis, Modalverben, German